Uso da Luffa cylindrica como meio suporte para crescimento bacteriano em filtro anaeróbio tratando esgotos domésticos - Fernandes, William Vieira (2012)
The remoteness from urban centers, in general, is the most responsible for the not economically feasible implementation of a sewage disposal system. Simplified and high benefit/cost ratio systems may prove very useful as sanitary solution. In Brazil, anaerobic filters have been often used in septic tank sequence for the soluble fraction effluent's treatment, given technical and economic criteria. The use of Luffa cylindrica, or loofah sponge, as support media in anaerobic reactors, particularly in biofilters, still requires further investigation. The objective of this study was to investigate the feasibility of using this material in anaerobic filters as a low cost alternative for domestic sewage treatment. A system consisting of septic tank, flow divider box and anaerobic filters in parallel was built at the campus I UFPB. The filter F1 was filled with loofah sponge, the F2 with conduit chips and F3 with stone. Monitoring of flow and physical-chemical parameters of effluent was made during one year. Efficiencies were obtained in the order of 37.5%, 36.2% and 52.1% in BOD removal and 44.4%, 34.4% and 40.0% for COD removal for the F1, F2, and F3 filters respectively. There was no noticeable degradation in loofah sponge. It can be concluded that the systems performance was similar, indicating that Luffa cylindrica can be used as alternate support media in anaerobic filters.